Kreativitas Dalam Perspektif Teori Humanistik Rogers - Muhammad Qorib; Parjuangan Parjuangan; Canra Krisna Jaya (UMSU, 2022)
Rogers is one of humanism figure who views human as a tough and creative individual to develop him self. His educational background really influence the way he thought and his theory. His most famous theory was client centered. In the theory, a client is considered as a honored and possessed super power within his body. Therapist in this theory is seen like a real friend who is trying to position him and his client without distance nor boundaries. This is intended so that the client is willing to communicate his main problems freely. The goal is to discover his client potential talent owned. This theory will be effectively applied in educational field recently. Within this, students are expected to grow and develop according to their interest and talents, without any outside force. The expected outcome is that the students will become golden individual who have more humanity and creative as well.